Carbonized Copolymers Nonwoven Nanofibers Composite: Surface Morphology and Fibers Orientation - I. Waisi, Basma (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
Carbonized nonwoven nanofibers composite were fabricated using the electrospinning method of a polymeric solution composite followed by heat treatment including stabilization and calcination steps. The spun polymeric solution was a binary polymer mixture/organic solvent. In this study, two types of polymers (Polymethylmethacrylate (PMMA) and Polyethylene glycol (PEG)) were used separately as a copolymer with the base polymer (Polyacrylonitrile (PAN)) to prepare a binary polymer mixture in a mixing ratio of 50:50. The prepared precursor solutions were used to prepare the precursor nanofibers composite (PAN: PMMA) and (PAN: PEG). The fabricated precursors nonwoven fibers composite were stabilized and carbonized to produce carbon nonwoven nanofibers composite. The effect of the combined polymer type on the fiber size, fiber size distribution, and surface morphology of the prepared nonwoven nanofibers was studied. The nonwoven fibers orientation and surface morphology were characterized using field emission scanning electron microscope (FESEM). In addition, ImageJ software has been used to calculate the fiber size and fiber size distribution. Here, the obvious effect of the copolymer type on the surface morphology, fiber size, and fiber orientation has been demonstrated. Using a copolymer with PAN polymer led to increasing the fiber size. The carbonized nanofibers composite prepared using PEG polymer as a copolymer was more ordered fibers in comparison with the fiber orientation of carbon nanofibers based on pure PAN. In contrast of that, using PMMA as a copolymer resulted curly carbonized nonwoven nanofiber composite.